MODERN DRESSING WOUND CARE EFFECTIVE HEALING DIABETIC Wounds IN ISAM CAHAYA HOLISTIC CARE - Sudarman Sudarman; Akbar Asfar; Haeril Amir (LLDIKTI Wilayah X, 2020)
Diabetes mellitus has a risk of causing complications, one of which is diabetic foot injury. The nurse who plays the role of nursing care is very important in the process of healing diabetic wounds. Wound care with modern wound dressing methods can prevent infection in diabetic foot sores and is effective against the process of healing diabetic wounds. This study aims to determine the effect of modern dressing dressing treatment methods on diabetic wound healing in the Independent Nursing Practice of Isam Cahaya Holistic Care Makassar City. The research design used was observational analytic with a pre-experimental design approach without pretest-posttest design. Sampling was done by accidental sampling with a sample of 15 people. The results of the Wilcoxon test with significance level ρ <α = 0.05. The results showed that there was an average difference between the results of the condition status / wound healing before and after the wound treatment of the modern dressing method with a value of ρ = 0.001. The conclusion of this study is that the wound dressing modern method affects the healing of diabetic wounds in the Independent Nursing Practice of Isam Cahaya Holistic Care Makassar City. It is expected that nurses can improve their knowledge and skills about wound care with modern dressing methods to be able to provide appropriate and quality wound care.